Penyelesaian Wanprestasi atas Dasar Force Majeure Akibat Pandemi Covid-19 dalam Perjanjian Pembiayaan Konsumen - Made Bagus Rizal Raysando; Ni Komang Arini Setyawati; Desak Gde Dwi Arini (Warmadewa Press, 2021)
Consumer finance is a financing institution that is officially still relatively new in Indonesia. Consumer financing agreements are agreements that arise in the day-to-day practice of the wider community. In a contractual relationship, the Covid-19 pandemic has become a point of debate between business actors who are bound by the contract. Debtors who have contractual obligations make the Covid-19 pandemic a basis for freeing themselves from their obligations to fulfill achievements. The purpose of this research is to find out the legal basis for the arrangement of consumer financing agreements in the perspective of contract law and to find out the consequences of force majeure for the parties to the consumer financing agreement in the event of a Covid-19 pandemic. The problems contained in this research are how the legal basis for the regulation of consumer financing agreements in the perspective of contract law and what are the consequences of force majeure for parties to the consumer finance agreement in the event of a corona virus outbreak. The method used is a normative research method by using a statutory approach and a conceptual approach. Based on the results of this study, it can be concluded that the Covid-19 pandemic currently occurring can only qualify as a forced condition which is not absolute or relative or it can be said that the debtor cannot make the reason for this pandemic as a reason for contract cancellation. This relative coercion is limited to delaying the implementation of the obligation to fulfill the achievement for a while, whereby the parties can negotiate the agreements that have been previously made.